2021
DOI: 10.7554/elife.69866
|View full text |Cite
|
Sign up to set email alerts
|

Convalescent plasma use in the USA was inversely correlated with COVID-19 mortality

Abstract: Background. The US Food and Drug Administration authorized Convalescent Plasma (CCP) therapy for hospitalized COVID-19 patients via the Expanded Access Program (EAP) and the Emergency Use Authorization (EUA), leading to use in about 500,000 patients during the first year of the pandemic for the US.Methods. We tracked the number of CCP units dispensed to hospitals by blood banking organizations and correlated that usage with hospital admission and mortality data.Results. CCP usage per admission peaked in Fall 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
47
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 44 publications
2
47
0
1
Order By: Relevance
“…to the reduction of mortality for COVID-19 observed during the different waves in our hospital in low-intensity departments (from 21.9% in the first wave to 12.7% in the third wave) in a recently published analysis [ 15 ]. A similar finding, i.e., a strong inverse correlation between CCP use and mortality per hospital admission, was also observed in a recent publication reporting the US experience on EAP use of CCP in approximately 500,000 patients [ 24 ].…”
Section: Discussionsupporting
confidence: 83%
“…to the reduction of mortality for COVID-19 observed during the different waves in our hospital in low-intensity departments (from 21.9% in the first wave to 12.7% in the third wave) in a recently published analysis [ 15 ]. A similar finding, i.e., a strong inverse correlation between CCP use and mortality per hospital admission, was also observed in a recent publication reporting the US experience on EAP use of CCP in approximately 500,000 patients [ 24 ].…”
Section: Discussionsupporting
confidence: 83%
“…During the SARS-CoV-2 pandemic, preliminary results from several therapeutic options have raised hopes that subsequent clinical experiences have revealed to be wrong [10] . Moreover, concerning the CCP efficacy, the lack of univocal evidence is probably due to the variety of experimental designs reported in the literature, and even today it is not certain whether it could still give a relevant contribution to the treatment of COVID-19 ( Table 1 ) [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] . A randomized controlled trial has been also conducted on 487 patients in Italy, named TSUNAMI Study ( TranSfUsion of coNvalescent plAsma for the treatment of severe pneuMonIa due to SARS-CoV-2 ), under the patronage of the Italian Medicine Agency (AIFA) and the Italian National Institute of Health (ISS), whose definitive results are not yet published.…”
Section: Introductionmentioning
confidence: 99%
“… [16] UK May 2021 RECOVERY trial, RCT Intervention: 5795 patients, control group: 5,763 patients Moderately/ critically ill patients Among patients hospitalised with COVID-19, high-titre CCP did not improve survival or other prespecified clinical outcomes. Casadevall et al [17] USA June 2021 Retrospective 500,000 patients All clinical conditions CCP use in the USA was inversely correlated with COVID-19 mortality. Körper et al [18] Germany October 2021 Randomized 1:1 Intervention: 53 patients, control group: 52 patients Critically ill patients No significant improvement in CCP treated patients.…”
Section: Introductionmentioning
confidence: 99%
“…In a randomized trial focusing on inpatient adults with mild disease who were greater than 75 years of age or 65 with comorbid conditions, Libster et al found that CIP was protective of progression to severe disease ( 17 ). Finally, an analysis of CIP usage and mortality across the pandemic showed an inverse correlation, suggesting that CIP saves lives ( 23 ). In contrast, several randomized controlled trials have either terminated early due to low enrollment or found no benefit of CIP ( 13 , 24 26 ).…”
Section: Discussionmentioning
confidence: 99%